BLENDED LEARNING ENVIRONMENT: PROMOTING LEARNERS' SELF-EFFICACY - Puspitasari, Desi (Institut Agama Islam Negeri Ponorogo, 2021)
In recent years, blended learning has been utilizing in a variety of contexts. It emerges as one of the most popular pedagogical approaches which integrate face-to-face classes with the virtual learning environment. It offers learners considerable resources and materials. Many researchers have reported on it since it thrived. It offers learners flexibility. It also gives the learners choices about when and where they learn and participate in online learning. Therefore, it is used for teaching and training worldwide since many researchers found it an effective way to be used in the teaching-learning process. It is believed to enhance learners' understanding of learning a foreign language. Some researchers also found that blended learning affects learners' self-efficacy stronger than the other instructional modes. This study employed qualitative research. It was used to determine how blended learning was applied in a class to boost learners' self-efficacy. In conclusion, the developments of technology recently encourage educators to apply a blended learning environment in the classroom. One of the important things is how it should be implemented to help the learners develop their self-efficacy and achieve their academic goals.